Binocular contributions to motion detection and motion discrimination during locomotion. - Hongyi Guo; Robert S Allison (PLoS ONE)
During locomotion, the visual system can factor out the motion component caused by observer locomotion from the complex target flow vector to obtain the world-relative target motion. This process, which has been termed flow parsing, is known to be incomplete, but viewing with both eyes could potentially aid in this task. Binocular disparity and binocular summation could both improve performance when viewing with both eyes. To separate the binocular disparity and binocular summation and analyse how they affect flow parsing, we tested detection and discrimination thresholds under three viewing conditions: stereoscopic, synoptic (binocular but without disparity) and monocular. Experiment 1 tested motion detection during simulated forward self-motion and when stationary. Experiment 2 and 3 tested motion discrimination in forward and backward self-motion and stationary conditions. We found that binocular disparity significantly improved detection thresholds and discrimination biases, at the cost of lower precision. Binocular summation only significantly improved detection thresholds when stationary. It did not significantly affect detection thresholds during locomotion, discrimination biases, or discrimination precisions. Our results indicated that both binocular summation and binocular disparity contribute to motion detection and motion discrimination, but they affect performance differently while stationary and during locomotion.